The Implementation of Token Economy in Behavior Modification to Improve Sleep Quality of Drug Abuse Clients in the Recovery Process - Ambarwati, Septiana; Nuriyyatiningrum, Nadya Ariyani Hasanah; Wening Wihartati (Jurnal Psikologi Terapan, 2025)
Substance abuse has a serious impact on the sleep quality of clients undergoing rehabilitation, often resulting in insomnia and other sleep disturbances that can hinder the recovery process. Poor sleep quality may exacerbate psychological conditions and increase the risk of relapse. This study aims to examine the effectiveness of implementing a token economy as a behavioral modification method to improve the sleep quality of clients with substance use disorders during their recovery process. This research employed a mixed-method approach using a sequential exploratory design. The results showed an improvement in sleep quality among all three subjects after the implementation of the token economy. These findings suggest that the token economy is effective as a positive reinforcement strategy in modifying sleep behavior in clients with substance use disorders and may serve as an alternative approach to support the success of recovery programs.